The prevalence of obesity and related factors among primary and secondary school students - Deniz, S.; Oguzoncul, A. F. (Wolters Kluwer Medknow Publications, 2019)
Objectives: Obesity was previously seen as a problem in high-income countries. It is also a problem in low and middle-income countries today. The sedentary lifestyle has made this situation more pronounced. Childhood obesity continues in adulthood. Adequate and balanced nutrition and mobile lifestyle have a great role in the prevention and treatment of obesity. The aim of this study was to determine the prevalence of obesity among primary and secondary school students and related factors. Methods: The sample size was calculated as 1278 (213 x 6) for the gender distribution to be appropriate and for the primary and secondary school students to be included in the district center and villages. Considering 15% of the students' non-response rate, the number of students planned to be reached is 1500. Selection was made after the students were ranked by class, gender and place of residence. Of the 1500 students who were sampled, 1298 (86.53%) were evaluated. Results: There was no difference in body mass index between gender and place of residence. The prevalence of being overweight or obesity among secondary school students (25.2%) was significantly higher than primary school students (20.5%).Conclusion: In the childhood age group; sedentary lifestyle, having breakfast and obesity in parents had a significant effect on obesity. It is considered important for children and family members to have proper nutrition and mobile life behaviors.
Keywords: Childhood; obesity; overweight; primary school; secondary school